2016
DOI: 10.4137/cmc.s38328
|View full text |Cite
|
Sign up to set email alerts
|

Nearly Asymptomatic Eight-Month Thoracic Aortic Dissection

Abstract: Thoracic aortic dissection is a rare, but lethal, medical condition that is either misdiagnosed as a myocardial infarction or overlooked completely. Though thoracic aortic dissections are commonly diagnosed in patients exhibiting sharp chest pain, there are some notable cases where patients do not report the expected severity of pain. We report a unique case of a patient with a thoracic aortic dissection who was initially nearly asymptomatic for eight months, in order to heighten awareness, highlight diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…We eliminated the articles about cases that were not completely asymptomatic (eg, patients who actually had mild symptoms or painless or insidious symptoms). [1][2][3] We finally took on 13 cases of asymptomatic AD (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16] Their main features were as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…We eliminated the articles about cases that were not completely asymptomatic (eg, patients who actually had mild symptoms or painless or insidious symptoms). [1][2][3] We finally took on 13 cases of asymptomatic AD (Table 1). [4][5][6][7][8][9][10][11][12][13][14][15][16] Their main features were as follows:…”
Section: Literature Reviewmentioning
confidence: 99%
“…We searched for case reports of asymptomatic AD in PubMed and Web of Science, in English, using the following key words: asymptomatic, silent, painless, AD. We eliminated the articles about cases that were not completely asymptomatic (eg, patients who actually had mild symptoms or painless or insidious symptoms) 1‐3 . We finally took on 13 cases of asymptomatic AD (Table 1).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Aneurysms are usually silent unless an imaging study happens to have been performed; thus, true incidence is hard to estimate. Lethal thoracic aortic dissections are also often misdiagnosed as myocardial infarctions [4]. A local study reported that ruptured aortic aneurysm has a higher mortality rate than myocardial infarction (MI) wherein 75 to 80 percent with ruptured aortic aneurysm die compared to 10 to 20 percent of people coming with MI.…”
Section: Case Protocolmentioning
confidence: 99%
“…Asymptomatic AD is extremely rare. It has been reported occasionally and was diagnosed mostly by transesophageal echocardiography (TEE) or contrast computed tomography (CT) [9][10][11][12] . We will discuss a case of long-segmental AD without any obvious symptom, with which, the patient presented to cardiovascular department complaining of exaggerated low diastolic blood pressure (DBP) and widened pulse pressure (PP) when measuring routine blood pressure (BP).…”
Section: Introductionmentioning
confidence: 99%